(untitled) (Islamic Sciences Journal, 2023)
The research deals with the issue of Satan’s abstention from Adam after Allah Almighty commanded him to prostrate to him, by studying the Qur’anic verses contained in this issue. The purpose of this study is to clarify the problematic issue of this prostration and the secret of Satan’s disobedience, and whether Iblis was right in his refusal to prostrate as raised by the skeptics with the aim of defaming Allah’s destiny and wisdom in his creation. Adam was afflicted with Satan, and Satan was afflicted with Adam. The first affliction of Iblis with Adam was that Allah favored Adam over Iblis, and commanded iblis to prostrate to Adam, but he refused and was arrogant, and insisted on his disobedience and arrogance, so he was among those who were expelled, cursed, and seen until the Day of Judgment. Adam was first tested by Satan and he whispered to him by eating from the forbidden tree, so he took him out of what was in him, and when it became clear to him, he repented to his Lord, so Allah repented and guided him. Satan’s position on the command to prostrate was a departure from obedience to Allah , and not rebellion against Allah . Rather, he refused to prostrate by Allah’s command also to clarify, and he also tried to research the invalidity of the suspicions about this issue as much as possible. This research is considered as a scientific effort in addressing the thorny issues and issues related to the life of every Muslim.